Reading Attitude, Reading Interest, and Reading Achievement among Eleventh-Grade Students - Ria Lestari; Gaya Tridinanti; Jenny Elvinna Manurung (Universitas Islam Ogan Komering Ilir Kayuagung, 2026)
The study aimed to determine whether students’ psychological factors, particularly their attitudes and interests toward reading, were significantly related to their academic performance in reading English texts. This study employed a quantitative correlational design. The population consisted of all eleventh-grade students at SMA Negeri 21 Palembang, with a total of 388 students, and a sample of 105 students was selected through cluster random sampling. Data were collected using two questionnaires and a reading test. The collected data were analyzed using Pearson Product-Moment correlation and multiple regression analysis to determine both partial and simultaneous relationships among the variables. The results showed that there was no significant correlation between reading attitude and reading achievement. Provides a concise summary of purpose, methods, results, and conclusions. The key statistics (r = 0.028, r = 0.377, R² = 0.143) are appropriately included. indicating that students with higher reading interest tended to achieve better reading performance. Furthermore, multiple regression analysis revealed a significant simultaneous relationship between reading attitude and reading interest toward reading achievement (r = 0.378, p = 0.000), with a combined contribution of 14.3%. These findings suggest that reading interest plays a more influential role in supporting students’ reading achievement.